Archiving Caribbean identity : records, community, and memory - Aarons, John A.; Bastian, Jeannette A.; Griffin, Stanley H. (London : Routledge, 2022)
Archiving Caribbean Identity highlights the "Caribbeanization" of archives in the region, considering what those archives could include in the future and exploring the potential for new records in new formats. Interpreting records in the broadest sense, the 15 chapters in this volume explore a wide variety of records that represent new archival interpretations. The book is split into two parts, with the first part focusing on record forms that are not generally considered "archival" in traditional Western practice. The second part explores more "traditional" archival collections and demonstrates how these collections are analysed and presented from the perspective of Caribbean peoples. As a whole, the volume suggests how colonial records can be repurposed to surface Caribbean narratives. Reflecting on the unique challenges faced by developing countries as they approach their archives, the volume considers how to identify and archive records in the forms and formats that reflect the postcolonial and decolonized Caribbean, how to build an archive of the people that documents contemporary society and reflects Caribbean memory, and how to repurpose the colonial archives so that they assist the Caribbean in reclaiming its history. Archiving Caribbean Identity demonstrates how non-textual cultural traces function as archival records and how folk-centred perspectives disrupt conventional understandings of records. The book should thus be of interest to academics and students engaged in the study of archives, memory, culture, history, sociology, and the colonial and postcolonial experience
IntroductionJohn A. Aarons, Jeannette A. Bastian, and Stanley H. GriffinPart I. Tangible and Intangible FormatsChapter 1. Soca and collective memory; Savannah Grass as an archive of Carnival Kai BarrattChapter 2. Jamaican twitter as a repository for documenting memory and social resistance: Listening to the "articulate minority"Norman MalcolmChapter 3. Singing Our Caribbean Identity: Programming the UWI, Mona Festival of the Nine Lessons with Carols Shawn R.A. WrightChapter 4. Archives "cast in stone": Memorials as memoryElsie E. AaronsChapter 5. Landscape as record: Archiving the Antigua Recreation GroundStephen ButtersChapter 6. Concert Dance in Barbados as Archive: Dancing the national narrativesJohn HunteChapter 7. Remembering an art exhibit: The Face of Jamaica, 1963-1964Monique Barnett-DavidsonChapter 8. Traditional and new record sources in geointerpretive methods for reconstructing biophysical history: Whither Withywood Thera Edwards and Edward RobinsonPart II. Collections Through a Caribbean LensChapter 9. Resistance in/and the Pre-Emancipation ArchivesTonia Sutherland, Linda Sturtz, and Paulette KerrChapter 10. Postcolonial philately as memory and history: Stamping a new identity for Trinidad and TobagoDesaray Pivott-NolanChapter 11. Recasting Jamaican sculptor Ronald Moody (1900-1984): An archival homecomingEgo Ahaiwe SowinskiChapter 12. St. Lucian memory and identity through the eyes of John Robert LeeAntonia Charlemagne-MarshallChapter 13. Crop Over and Carnival in the archives of Barbados and Trinidad and TobagoAllison O. RamsayChapter 14. Ecclesiastical records as sources of social history: The Anglican Church of Trinidad and TobagoJanelle DukeChapter 15. Erasure and retention in Jamaica's official memory: The case of the disappearing telegramsJames Robertson . Index
OCLC-licensed vendor bibliographic record.
Keywords: Archives -- Caribbean Area; Collective memory -- Caribbean Area; Caribbean Area -- History -- Sources; Caribbean Area -- Historiography; HISTORY -- Caribbean & West Indies -- General